2021
DOI: 10.3390/polym13132165
|View full text |Cite
|
Sign up to set email alerts
|

High-Power LED Units Currently Available for Dental Resin-Based Materials—A Review

Abstract: The pursuit of less time-consuming procedures led to the development of high-power light-curing-units (LCU) to light-cure dental-resin-based-materials. This review aims to describe high-power light-emitting-diode (LED)-LCUs, by a bibliometric systematization of in vitro and in vivo studies. The research-question, by PICO model, aimed to assess the current knowledge on dentistry-based high-power LED-LCUs by analyzing to what extent their use can promote adverse events on materials and patients’ oral condition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
11
0
2
Order By: Relevance
“…11 Consequently, the irradiance values alone are less reliable than power measurements, 36 and a single irradiance value alone cannot fully describe the output of an LCU. 34 This study also agrees with a previous study, where the authors reported no correlation between the cost of the LCU and their irradiance values, but there was a high positive correlation between the cost and the power output and tip diameter. 52 In general, the budget LCUs delivered a lower power.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…11 Consequently, the irradiance values alone are less reliable than power measurements, 36 and a single irradiance value alone cannot fully describe the output of an LCU. 34 This study also agrees with a previous study, where the authors reported no correlation between the cost of the LCU and their irradiance values, but there was a high positive correlation between the cost and the power output and tip diameter. 52 In general, the budget LCUs delivered a lower power.…”
Section: Discussionsupporting
confidence: 92%
“…Even LCUs that deliver a low irradiance can still photo-cure the top surface of the resin restoration to the extent that it will feel hard to the dental explorer. Consequently, the LCU should ideally be checked daily [34][35][36] to ensure that the LCU is functioning correctly before it is used on patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first light‐emitting diode (LED) based LCUs were considered to be ‘cool’ because they delivered a lower irradiance (approximately 240 mW/cm 2 ) than the quartz tungsten halogen based LCUs (approximately 450–1200 mW/cm 2 ) 8 . Many LED lights now deliver irradiances greater than 2000 mW/cm 2 , and some manufacturers claim that exposure times shorter than 5 s may be used to reduce photo‐cure RBCs and reduce clinical time 13 . However, such high irradiance values have become a concern due to the potential risk to the soft tissues 14 and the dental pulp 10,15 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Many LED lights now deliver irradiances greater than 2000 mW/cm 2 , and some manufacturers claim that exposure times shorter than 5 s may be used to reduce photo-cure RBCs and reduce clinical time. 13 However, such high irradiance values have become a concern due to the potential risk to the soft tissues 14 and the dental pulp. 10,15 Using monkeys, Zach and Cohen in 1965 16 reported that an increase in PT of 5.5 C resulted in pulpal necrosis in 15% of the cases, and a temperature rise (ΔT) of 11 C resulted in pulpal necrosis in 60% of the cases.…”
Section: Introductionmentioning
confidence: 99%